HUBUNGAN TINGKAT PENGETAHUAN IBU TENTANG MAKANAN SEHAT DAN STATUS SOSIAL EKONOMI KELUARGA DENGAN KEJADIAN KARIES DENTIS PADA ANAK SEKOLAH DASAR DI KECAMATAN TANJUNG SENANG BANDAR LAMPUNG - Fadilla, Mirafzur Haris; Agustina, Rita; Mustofa, Festy Ladyani; Sjahriani, Tessa (Jurnal Ilmu Kedokteran dan Kesehatan, 2023)
Dental caries is a disease that affects about 90% of children. According to Suwelod, caries is influenced by external and internal factors. One component of external factors is the behavior of maintaining dental health as measured by the level of knowledge of the mother and socioeconomic status. Knowing the relationship between the level of knowledge of the mother and the socio-economic status of the family in elementary school children in the Tanjung Bahagia District, Bandar Lampung City. This type of research is quantitative analytic with cross-sectional research design, patience and self-efficacy questionnaire with stratified random sampling technique. There were 100 mothers with good level of knowledge, 58 children (58%), the highest socioeconomic status level in the <UMR category, 74 respondents (74%), the highest incidence of dental caries was experienced by dental caries, namely 72 children (72 %) Statistical analysis used the chi-square test on the frequency of consumption of packaged milk and the incidence of dental caries with a value of p = 0.735 and a correlation value of OR = 1.169, on the level of knowledge of mothers and the incidence of dental caries. with a value of p = 0.06 and a correlation value of OR = 2.459. There is no significant relationship between the level of knowledge of the mother and the incidence of caries, however, there is a significant relationship between socioeconomic status and the incidence of caries in elementary school children in Tanjung Bahagia District, Bandar Lampung